Entrepreneurial Team Composition Characteristics and New Venture Performance: A Meta–Analysis - Jin, Linlin; Madison, Kristen; Kraiczy, Nils D.; Kellermanns, Franz W.; Crook, T. Russell; Xi, Jing (Entrepreneurship Theory and Practice, 2017)
Upper echelon theory highlights the importance of top management teams in large and established firms; however, effects are not always clear outside of this context. Due to the unique nature of new ventures, the composition of entrepreneurial teams and its effects on performance is worthy of investigation. Accordingly, we meta–analyze the effect of three characteristics of entrepreneurial team composition (i.e., aggregated, heterogeneity, team size) on new venture performance. Our meta–analysis, which includes 55 empirical samples and 8,892 observations, finds significant and unique effects of entrepreneurial team characteristics on new ventures. Based on our findings, we derive avenues for future research.